The evolution of church leadership in the New Testament - a new consensus? - Zyl, Hermie C. van (Neotestamentica, 1998)
Campbell in his book, The elders: Seniority within earliest Christianity (1994). proposes a 'new consensus' in viewing the evolution of church leadership in the New Testament. He utilises the results of the sociological approach to the New Testament in an attempt to establish a link between the term presbuteros and the paterfamilias figure of the house churches in the Pauline churches. In so doing he asserts that the evolution of church leadership should not be viewed in terms of a decline from charismatic to ecclesiastical leadership (the 'old' consensus). In this article it is maintained that the church had 'natural' leaders since its inception. This leadership then matured into the hierarchical church order of the second century, of which the letters of Clement of Rome and Ignatius of Antioch bear early testimony. The article concludes with a brief appraisal in which certain deficiencies of Campbell's 'new consensus' are pointed out.